Kontribusi Nahdlatul Ulama dalam Pengembangan Pendidikan di Indonesia Pasca-Kemerdekaan: Sebuah Kajian Sejarah dan Transformasi Sosial - Ima Rosila; Abdul Khobir (Jurnal Nakula : Pusat Ilmu Pendidikan, Bahasa dan Ilmu Sosial, 2025)
Nahdlatul Ulama (NU), as the largest religious organization in Indonesia, has a strategic role in building the education system in Indonesia after independence. This article aims to examine NU's contribution to the development of education through historical and social transformation perspectives. This study uses a qualitative approach with a literature study method, analyzing various historical documents, education policies, and relevant literature. The results of the study show that NU not only contributes to pesantren-based education, but is also active in establishing formal educational institutions, is involved in the formation of the national curriculum, and promotes the values ​​of pluralism and nationalism in education. This article emphasizes the importance of understanding NU's historical role in order to appreciate its impact on social and educational dynamics in Indonesia.